2005
DOI: 10.1017/s0031182004006985
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation by a high molecular weight fraction from the rat tapeworm Hymenolepis diminuta

Abstract: The host-parasite relationship is exquisitely specific. In exploiting the host niche, a variety of helminth parasites have been shown to directly manipulate their hosts' immune responses. We assessed the ability of a whole-worm extract of Hymenolepis diminuta to modulate immune cell activation. Immune cells isolated from human blood or rodent spleens were activated with the T cell mitogen, concanavalin A (Con A) +/- H. diminuta extract and cytokine production (i.e. IL-2, -4, -10, -12) and proliferation assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…In this and other studies (Isaak 1983;Palmas et al 1984Palmas et al , 1986Gabriele et al 1986;Shinoda and Asano 1989;Mangoud et al 1991;Claveria et al 2005;Wang and McKay 2005), only small alterations were recorded in the rat adrenal glands during experimental hymenolepiasis. The changes take place essentially in zona fascicularis (Palmas et al 1984, present study), the adaptive reaction of which is the mobilization of cytoplasmatic lipids in connection with the steroid hormone synthesis.…”
Section: Stanis³asupporting
confidence: 51%
See 1 more Smart Citation
“…In this and other studies (Isaak 1983;Palmas et al 1984Palmas et al , 1986Gabriele et al 1986;Shinoda and Asano 1989;Mangoud et al 1991;Claveria et al 2005;Wang and McKay 2005), only small alterations were recorded in the rat adrenal glands during experimental hymenolepiasis. The changes take place essentially in zona fascicularis (Palmas et al 1984, present study), the adaptive reaction of which is the mobilization of cytoplasmatic lipids in connection with the steroid hormone synthesis.…”
Section: Stanis³asupporting
confidence: 51%
“…As demonstrated by Wang and McKay (2005), H. diminuta could block the activation of the T-cell proliferation by interleukin-4 inhibition. The T-cell inhibition was also observed in hymenolepiasis caused by R. nana (Shinoda and Asano 1989).…”
Section: Introductionmentioning
confidence: 93%
“…Using DNBS to evoke what is considered a Th1-driven colitis (24), the present study shows that H. diminuta infection in a prophylactic regimen almost abolished the colitis, as assessed by clinical parameters, histological assessment, and biochemical markers (i.e., MPO). One interpretation of the data is that H. diminuta ameliorates colitis via the release of a particular factor, and indeed, like other parasitic helminths (25), H. diminuta Ag can block mitogen-driven T cell responses in vitro (26). However, in the nonpermissive murine system, the helminth never establishes or attains a significant biomass (15).…”
Section: Discussionmentioning
confidence: 99%
“…Adult H. diminuta worms were flushed from the small intestine of rats and rinsed (four times) in normal saline at room temperature (45). Then, 20-g (wet weight) portions of H. diminuta were transferred into 20-ml portions of sterile PBS and homogenized on ice at maximum speed for 5 min by using a Polytron PT1200 homogenizer (Kinematica, Inc., New York, NY).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that a crude extract of H. diminuta significantly reduced proliferation and cytokine production by human and murine T cells (45). Reasoning that the immunosuppressive effect need not be restricted to T cells, the present study assessed the ability of a high-molecular-mass fraction from adult H. diminuta (HdHMW) and excreted and/or secreted products (HdES) to block macrophage activa-tion, as assessed mainly by tumor necrosis factor alpha (TNF-␣) production.…”
mentioning
confidence: 99%